Towards DNA‐Encoded Micellar Chemistry: DNA‐Micelle Association and Environment Sensitivity of Catalysis. Issue 39 (7th June 2021) - Klika Škopić, Mateja; Gramse, Christian; Oliva, Rosario; Pospich, Sabrina; Neukirch, Laura; Manisegaran, Magiliny; Raunser, Stefan; Winter, Roland; Weberskirch, Ralf; Brunschweiger, Andreas
Abstract: The development of DNA‐compatible reaction methodologies is a central theme to advance DNA‐encoded screening library technology. Recently, we were able to show that sulfonic acid‐functionalized block copolymer micelles facilitated Brønsted acid‐promoted reactions such as the Povarov reaction on DNA‐coupled starting materials with minimal DNA degradation. Here, the impact of polymer composition on micelle shape, and reaction conversion was investigated. A dozen sulfonic acid‐functionalized block copolymers of different molar mass and composition were prepared by RAFT polymerization and were tested in the Povarov reaction, removal of the Boc protective group, and the Biginelli reaction. The results showed trends in the polymer structure‐micellar catalytic activity relationship. For instance, micelles composed of block copolymers with shorter acrylate ester chains formed smaller particles and tended to provide faster reaction kinetics. Moreover, fluorescence quenching experiments as well as circular dichroism spectroscopy showed that DNA‐oligomer‐conjugates, although highly water‐soluble, accumulated very effectively in the micellar compartments, which is a prerequisite for carrying out a DNA‐encoded reaction in the presence of polymer micelles. Abstract : It′s a matter of environment : Copolymer micelles attracted DNA oligonucleotide conjugates in aqueous solution despite lacking canonical DNA‐binding motifs. Following accumulation inside micelles, DNA‐coupled starting materials underwent Povarov and Biginelli reactions to target molecules by a localized sulfonic acid. The kinetics of a given reaction were tuned by the chemical environment within the micelles.